Role of parenting style and parents’ education in positive youth development of adolescents - Kiadarbandsari, A.; Madon, Z.; Hamsan, Hanina Halimatusaadiah; Mehdinezhad Nouri, K. (Universiti Putra Malaysia Press, 2016)
The main purpose of this research is to determine the role of parenting style and educational level of parents in Positive Youth Development (PYD). Data were obtained using a questionnaire method involving 496 adolescent students of national secondary schools in Selangor. The findings indicate that there is a significant difference between the means for different races in PYD. This study also revealed that authoritative parenting styles, uninvolved parenting styles, and fathers’ level of education are significantly correlated to PYD. The authoritative parenting style was found to be the most significant predictor of higher PYD. These findings suggest that adolescents with authoritative parents in Malaysia show higher PYD and accordingly, they contribute to self, others and community.